Developing professional networks: the missing link to graduate employability. Issue 4 (23rd February 2021) - English, Peter; de Villiers Scheepers, Margarietha Johanna; Fleischman, David; Burgess, Jacqueline; Crimmins, Gail
Abstract : Purpose: Responding to increasing external pressure, universities are developing new strategies to illustrate the impact of their degrees on graduate employability. This paper investigates how alumni regard the development of their professional networks during their tertiary education in relation to employability and the associated pedagogical implications. Design/methodology/approach: A qualitative approach using semi-structured interviews with 18 business and arts alumni from a regional university. Findings: The findings reveal the importance of developing a professional network by cultivating social capital while at university. Alumni identify all forms of work-integrated learning (WIL), connectedness through social media, the role of university staff and volunteering as concrete ways to develop a professional network and enhance employability. Research limitations/implications: This paper has pedagogical implications to develop graduate employability and WIL. Universities should draw from alumni networks to help develop students' bridging capital through industry-facing WIL projects. Educators should design assessment tasks in which students develop contacts and networking capabilities with alumni and other professionals using various platforms (e.g. social media). In addition, educators should promote the benefits of voluntary work and invite alumni and other industry stakeholders to co-design and co-teach areas of curriculum. Originality/value: Drawing from the experiences of alumni re-routes the channel of communication from institutions expressing the importance of professional networks in relation to employability, to credible industry alumni confirming this importance. Few previous studies have taken this "outside-in approach" to emphasise and validate the importance of developing professional networks in relation to employability, particularly at regional universities.